Plant Diversity in Khok Sam Rong Community Forest, Dan Khun Thod District, Nakhon Ratchasima Province - Choopan, Thiamhathai (YRU Journal of Science and Technology, 2022)
Plant diversity in Khok Sam Rong Community Forest, Dan Khun Thod District, Nakhon Ratchasima Province was studied using 20´20 meter and 5´5 meter of 14 sampling plots for tree and understory plant, respectively. Forty-nine families, 111 genera, 125 species were found. The highest important value index of tree was Memecylon edule Roxb., Lannea coromandelica (Houtt.) Merr., Sindora siamensis Teijsm. ex Miq., and Bauhinia saccocalyx Pierre. The highest important value index of understory was Memecylon edule Roxb., Vietnamosasa pusilla (A. Chev. & A. Camus) T.Q. Nguyen, Croton crassifolius Geiseler, and Rhynchosia bracteata Benth. ex Baker, respectively. Species diversity index of tree and understory were 3.0471 and 3.4000. Evenness values were 0.7570 and 0.7575, respectively. The most diverse families were Fabaceae (17 species), Phyllanthaceae and Poaceae (6 species), Apocynaceae, Lamiaceae, Malvaceae, and Rubiaceae (5 species). Endemic species is Jasminum siamense Craib.